Bacteriological and PCR analysis of clinical material aspirated from otitis media with effusions - Gok, U; Bulut, Y; Keles, E; Yalcin, S; Doymaz, MZ (Elsevier Ireland Ltd, 2001)
Otitis media with effusions (OME) can lead to significant hearing loss in childhood. Although previous studies have shown that bacterial DNA is present in a significant percentage of effusions sterile by culture, whether the DNA represents viable organisms or 'fossilized remains' is unknown. The aim of the present study was the determination of Streptococcus pneumonia, Moraxella catarrhalis and Haemophilus influenza in the clinical materials from OME. For this purpose, effusion samples aspirated from the mid-ear were analyzed bacteriologically. Samples were also tested with polymerase chain reaction (PCR) assay. A total of 37 samples obtained from 20 patients aging between 4 and 14 were analyzed. In 17 patients, both ears demonstrated effusions, whereas in three patients, only one ear had effusions. In aerobic bacterial culture assays, nine samples (24.3%) showed bacterial growth. None of the samples were positive for anaerobic culture experiments. PCR analysis of the samples showed that 35 samples (94.5%) contained bacterial DNA, In 19 samples, only one bacterial species and in 16 samples more than one bacterial species were detected. The results of this study demonstrate that effusion fluid from otitis media cases contain a battery of bacterial species and these bacteria might play roles in the pathogens of OME. Our results indicate the PCR technique is more specific and sensitive in detection of bacteria in middle-ear effusion of OME, compared with conventional methods. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: otitis media with effusion; bacteria; PCR